Mechanical properties of electro and butt fusion welded high-density polyethylene pipes - Alkaki, Soran Saleem; Kaman, Mete Onur (Carl Hanser Verlag, 2019)
Electrofusion welding and butt fusion welding are common methods for joining polyethylene pipes used for water and gas distribution. Because of the wide use of these two methods in infrastructure engineering, welded pipe joints and pipe materials should be examined with the intent of reducing errors in projects. The purpose of this study is to increase knowledge of electrofusion and butt fusion welding methods and examine them in order to establish which offers the best performance for a specific engineering service project. Tensile and hydrostatic pressure tests are performed on un-welded and welded pipes for high-density polyethylene pipes. Additionally, a numerical analysis of the experimental results is conducted by employing the ANSYS program for tensile test samples. In tensile tests, according to the maximum average load, electrofusion welding values are larger than those of butt fusion welding and the elongations of the un-welded pipe at the fracture in butt fusion welding are greater than in electrofusion welding. For short-term hydrostatic pressure tests, the resistance in butt fusion welding for defects of roundness and alignment is better than that of electrofusion welding.
Keywords: Electro fusion welding; high density polyethylene; tensile test; hydrostatic pressure test; finite element method